Investigation into first year students adjustment to university at the Faculty of Cognitive Sciences and Human Development - Che Nur Syafiqkah, Binti Mohamad Fuzi. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Fifty seven percent of dropouts from Malaysian Universities are dissatisfied with their university life since their first year. This study aims at finding out first year students' adjustment to university, specifically those enrolled full time at the Faculty of Cognitive Sciences and Human Development (FCSHD). The objective of this study is to identify the overall adjustment level experienced by first year students at the faculty. The study investigates if there is a significant difference in different djustment sub-scales based on gender, socio-economic status and place of origin. The different adjustment sub-scales encompass of academic adjustment, social adjustment, personal-emotional adjustment, and goal commitment-institutional attachment. The study used quantitative survey method to collect data from 82 respondents who are first year full time students at the faculty. The instrument used was Student Adaptations to College Questionnaire (SACQ) by Baker and Syrik that consists of 67 items. Independent sample t-Test and Analysis of Variance (ANOVA) were used to analyse the data. Findings indicate that there is no significant difference in different adjustment sub-scales based on gender, socio-economic status and places of origin.